I am kind a positive power story - Capozzi, Suzy; Unten, Eren Blanquet; Random House Children's Books (New York Random House, 2017)
I Am Kind follows a little girl who sees kindness all around her. Her mother is kind when she volunteers in the community, and her neighbor is kind when he gives her strawberries from his garden. Even her nature troop is kind when they take care of the earth! The little girl realizes that she, too, has the power to be kind, and that even small actions can have a big impact. In this new installment of the Positive Power early reader series, children will learn the affirmation I am kind through an encouraging story of community and everyday kindness
"Originally published by Rodale Kids, an imprint of Random House Children's Books ... in 2017"--Copyright page
English Stories
F&P text level H
Keywords: Conduct of life -- Juvenile fiction; Etiquette -- Juvenile fiction; Families -- Juvenile fiction; Kindness -- Juvenile fiction; Mothers -- Juvenile fiction; Thoughtfulness -- Juvenile fiction; Behavior -- Fiction; Etiquette -- Fiction; Family life -- Fiction; Kindness -- Fiction; Mothers -- Fiction; Thougthfulness -- Fiction; Conduct of life; Etiquette; Families; JUVENILE FICTION / Readers / Beginner; JUVENILE FICTION / Social Themes / Friendship; JUVENILE FICTION / Social Themes / Values & Virtues; Kindness; Mothers; Thoughtfulness; Children's stories; Readers; Fiction; Juvenile works; Readers (Publications); Readers (Publications); Readers; readers